Aging induces cardiac mesenchymal stromal cell senescence and promotes endothelial cell fate of the CD90 + subset. Issue 5 (29th July 2019) - Martini, Hélène; Iacovoni, Jason S.; Maggiorani, Damien; Dutaur, Marianne; Marsal, Dimitri J.; Roncalli, Jerome; Itier, Romain; Dambrin, Camille; Pizzinat, Nathalie; Mialet‐Perez, Jeanne; Cussac, Daniel; Parini, Angelo; et al.
Abstract: Aging is a major risk factor in the development of chronic diseases, especially cardiovascular diseases. Age‐related organ dysfunction is strongly associated with the accumulation of senescent cells. Cardiac mesenchymal stromal cells (cMSCs), deemed part of the microenvironment, modulate cardiac homeostasis through their vascular differentiation potential and paracrine activity. Transcriptomic analysis of cMSCs identified age‐dependent biological pathways regulating immune responses and angiogenesis. Aged cMSCs displayed a senescence program characterized by Cdkn2a expression, decreased proliferation and clonogenicity, and acquisition of a senescence‐associated secretory phenotype (SASP). Increased CCR2‐dependent monocyte recruitment by aged cMSCs was associated with increased IL‐1ß production by inflammatory macrophages in the aging heart. In turn, IL‐1ß induced senescence in cMSCs and mimicked age‐related phenotypic changes such as decreased CD90 expression. The CD90+ and CD90‐ cMSC subsets had biased vascular differentiation potentials, and CD90+ cMSCs were more prone to acquire markers of the endothelial lineage with aging. These features were related to the emergence of a new cMSC subset in the aging heart, expressing CD31 and endothelial genes. These results demonstrate that cMSC senescence and SASP production are supported by the installation of an inflammatory amplification loop, which could sustain cMSC senescence and interfere with their vascular differentiation potentials. Abstract : Senescence of cMSCs shapes the cardiac microenvironment by CCR2‐dependent monocyte recruitment and emergence of a non conventional endothelial‐like cMSC subset.